Biomimetic Facade Design Proposal to Improving Thermal Comfort in Hot Climate Region - Avinc, Gune Mutlu; Koc, Seda Nur; Selcuk, Semra Arslan (Penerbit Utm Press, 2024)
The building envelope has an essential role in the energy consumption of buildings and in regulating the energy exchange between the indoor and outdoor environment. Especially in hot climate zones, the temperature increases the cooling loads of the building, while a significant amount of energy is consumed to provide indoor comfort. Much research has been carried out recently to produce responsive and adaptive building envelopes to solve this problem. Nature is a reference for responsive, adaptive building envelope solutions, and the biomimicry approach is utilized. The biomimicry approach suggests using biological models/systems/processes as models/measures/mentors. This research used the biomimicry approach to propose an innovative facade design solution in this context. In this study, where a problem-oriented design approach was accepted, plants were analyzed to find a solution. Plants have evolved to adapt to a particular location's weather, wind, dryness, heat, and light. Buildings, like plants, depend on a specific location. For this reason, arid climate plants were examined in the study. The biological information from analyzing the plants studied was used to develop a design concept. As a result of this study, it is understood that nature has an extensive database and offers many solutions for problems that can be applied in architecture to produce energy-efficient, sustainable, and adaptable designs to indoor and outdoor conditions. The next step for this study is to translate the developed design concept into practice and conduct the necessary analysis.
Keywords: Biomimicry; Biomimetic Design; Facade Design; Thermal Comfort